1990
DOI: 10.1046/j.1468-2982.1990.1006317.x
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Slow Potentials and Associated Catecholamine Function in Migraine

Abstract: Plasma norepinephrine and dopamine and event-related slow potentials were measured at menses and ovulation in migraine with and without aura relative to normal subjects. The results indicated that at menses, but not ovulation, plasma dopamine was increased and norepinephrine was decreased relative to normal. This catecholamine imbalance was greater in migraine without aura than in migraine with aura. Conversely, event-related slow potentials measured over the posterior cortex at ovulation but not at the menses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 40 publications
5
52
1
1
Order By: Relevance
“…Treatment with dopamine agonist can determine various responses [25]. Dopamine antagonists have been used successfully in acute migraine treatment [26], and there is evidence that alterations in dopamine may occur during migraine attacks [27]. Alteration of headache phenotypes after administration of dopamine agonists suggests that headache syndromes associated with prolactinomas may be the result of alterations in the dopamineprolactin axis rather than simply caused by the mass effects of the tumour, also because the headache begins months before hormonal symptoms for pituitary disorders appear [17,25].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with dopamine agonist can determine various responses [25]. Dopamine antagonists have been used successfully in acute migraine treatment [26], and there is evidence that alterations in dopamine may occur during migraine attacks [27]. Alteration of headache phenotypes after administration of dopamine agonists suggests that headache syndromes associated with prolactinomas may be the result of alterations in the dopamineprolactin axis rather than simply caused by the mass effects of the tumour, also because the headache begins months before hormonal symptoms for pituitary disorders appear [17,25].…”
Section: Discussionmentioning
confidence: 99%
“…DA plasma levels measured during the menses are higher in women with migraine without aura than in controls [9]. The DA metabolite 3,4-dihydroxyphenylacetic acid (DOPAC) increases in CSF during the migraine attack and increased levels correlate with pain severity [10].…”
Section: Biochemistrymentioning
confidence: 99%
“…In a postattack period after the use of sumatriptan, these patients showed improvements in selective attention~Mulder et al, 1999!, and a decrease in the early and late CNV that is confined to the frontal areas during a simple forewarned reaction time task~Mulder et al, 2001!. The CNV is thought to be controlled by noradrenergic and dopaminergic systems within the central nervous system~Libet, 1979; Maertens de Noordhout, Timsit-Berthier, Nagel-Leiby et al, 1990;Schoenen et al, 1986;TimsitBerthier, Mantanus, Poncelet, et al, 1986;Timsit-Berthier, Mantanus, Marissiaux, et al, 1986!, where noradrenergic pathways are believed to have a dominant role in the early wave, and dopaminergic structures mainly contribute to the late wave~Timsit-Berthier, Mantanus, Marissiaux, et al, 1986!. The serotonergic system might influence frontal attentional mechanisms through its effects on these central catecholaminergic systems.…”
Section: Ejcm Mulder Whjp Linssen and Ejc De Geusmentioning
confidence: 99%
“…Studies employing longer foreperiods predominantly report a larger early wave amplitude in migraine without aura~Böcker et al, 1990; Kropp & Gerber, 1993a;1993b; larger late wave amplitudes have also been reported~Böcker et al, 1990!. These augmented CNV amplitudes are believed to be a manifestation of cortical hyperexcitability, induced by hyperactive central catecholaminergic systems~Libet, 1979; Maertens de Noordhout et al, 1987;Nagel-Leiby, Welch, D'Andrea, Grunfeld, & Brown, 1990;Schoenen et al, 1986;Timsit-Berthier, Mantanus, Poncelet, Marissiaux, & Legros, 1986;Timsit-Berthier, Mantanus, Poncelet, et al, 1986!. In addition, the CNV appears to be sensitive to the temporal proximity of a migraine attack. The early wave increases even further during the days before an attack, but decreases to the level of healthy control subjects during an attack~Kropp & Gerber, 1995!.…”
mentioning
confidence: 97%